Increasing Critical Thinking Through the Blended Socratic Method of Teaching Model - Krismadinata, Krismadinata; verawardina, Unung; Jlinus, Nizwardi; Lubis, Arina Luthfini; Ramadhani, Dochi (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to determine the increase in student critical thinking from the Blended Socratic Method of Teaching (BSMT) model that is applied to visual programming courses, and determine the level of student satisfaction with the BMST model. This study uses the experimental method of choosing 1 class in the Informatics Engineering Education study program to be given a pretest, then applying the BMST model and finally to the posttest. Descriptive method is also used to determine the level of satisfaction with the BMST model. The instrument uses critical thinking skills and questionnaire tests to determine the level of student satisfaction. Collected data was analyzed with descriptive analysis techniques. The results showed a significant increase in students' critical thinking between pretest and posttest significantly. The results of the overall aspects of satisfaction with the BMST model applied showed a very satisfied category. It was concluded that the BMST model could increase student critical thinking and the level of satisfaction with the BMST model was very satisfied in the visual programming course. The renewal of the BMST model compared to other blended learning models is the existence of syntax to conduct case studies and percentage of case analysis, online and offline discussions with the concept of growing student critical thinking, the existence of monitoring discussions and the teacher's reaction to student responses.